COMPLIANCE WITH OCCUPATIONAL HEALTH AND SAFETY PRACTICES AMONG HEALTHCARE WORKERS IN VACCINATION UNITS: A CROSS-SECTIONAL STUDY IN BASRA, IRAQ - Fatima A. Najem; Alaa K. Jasim; Majid A. Maatook (International Journal Multidisciplinary (IJMI), 2026)
Objective: Healthcare workers (HCWs) in vaccination units are exposed to various occupational hazards, making adherence to occupational health and safety (OHS) measures essential. Therefore, this study aimed to assess OHS practices among HCWs in primary healthcare vaccination units in Basra Governorate, Iraq. Method: A descriptive cross-sectional study was conducted in 11 health sectors in Basra Governorate, Iraq, using a multistage stratified sampling approach with 228 HCWs. It depended on a questionnaire, which was designed based on a comprehensive review of relevant literature. Then, practice levels were categorized based on scores (poor and good). Results: Most HCWs demonstrated the highest compliance was observed for safe disposal of contaminated waste and sharps (93.0%), regular hand hygiene (89.0%), avoiding needle recapping (84.2%), post-exposure management (78.1%), and wearing protective gowns (55.7%). Lower compliance was identified for ergonomic practices (2.2%), safe lifting techniques (1.3%), consistent face mask use (3.5%), and regular glove replacement for each patient (7.5%). Novelty HCWs showed good OHS practices influenced by their residence and medical field.